Womens experience of Manual Vacuum Aspiration: An Irish perspective. (November 2021) - Hayes-Ryan, D.; Meaney, S.; Byrne, S.; Ramphul, M.; O'Dwyer, V.; Cooley, S.
Abstract: Objective: Manual Vacuum Aspiration (MVA) is a well-established management option for early pregnancy loss or early termination of pregnancy. MVA is performed as out-patient surgical procedure using local anaesthetic whereby aspiration of uterine contents is achieved through use of a hand-held negative pressure syringe. Ireland's first MVA service was established at the Rotunda Hospital Dublin in April 2020, . The purpose of this study was to gather feedback from women who had undergone MVA in the unit. Study design: Prospective mixed methods study of women attending for uterine aspiration under local anaesthetic from July to October 2020 in the unit. Consenting women were contacted one week following MVA via telephone. The survey conducted consisted of structured closed questions along with open-ended questions, to assess womens satisfaction in relation to all aspects of the MVA service. Results: Nineteen women took part in the study, a response rate of 86.4%. Participants reported feeling well informed prior to attending for MVA. Prior to the procedure, pain expectation scores were high but actual reported pain scores were much lower. Although some participants did find MVA uncomfortable, the fact the procedure was very quick and the side effects so minimal generally negated this. The location and set up of the clinic scored highly among participants as did the staff of the clinic. Overall satisfaction with the MVA service was high with 84.2% of participants reporting they would opt again for MVA in the future. Conclusions: Women living in Ireland are interested and agreeable with having Manual Vacuum Aspiration as an available option for management of early pregnancy complications. Consideration should be given to expansion of MVA services nationally.